Aging-resistant nylon modified material, preparation method and application thereof

CN121379129BActive Publication Date: 2026-11-03JIANGSU LEAD NEW MATERIAL TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202511568006.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-10-30
Publication Date
2026-11-03
Estimated Expiration
2045-10-30

AI Technical Summary

Technical Problem

Traditional nylon materials lack comprehensive aging protection in complex environments, have poor long-term effectiveness, are prone to nanoparticle aggregation, and have insufficient adaptability to various scenarios, making it difficult to meet the high-performance requirements of strategic emerging fields.

Method used

Functionalized nanocarriers are used to load anti-aging agents. The main antioxidant and ultraviolet absorber are loaded through mesoporous nanospheres. The formulation and process are optimized by combining the mesoporous channel slow-release effect and surface modification to achieve long-term slow release and uniform dispersion of anti-aging agents. The compatibility between the carrier and the nylon matrix is ​​improved by in-situ grafting process.

Benefits of technology

It achieves long-term protection of anti-aging agents, reduces processing volatilization and usage migration, improves the mechanical properties and application adaptability of materials, and expands the scope of applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application discloses an anti-aging nylon modified material and a preparation method and application thereof, and belongs to the field of high polymer material modification. The material is composed of a nylon base material, a functionalized nano carrier, an auxiliary antioxidant and a grafting monomer, the core of which is the self-made functionalized nano carrier, which is prepared through three steps of mesoporous sphere preparation, surface modification and anti-aging agent loading, and can realize long-acting slow release of the anti-aging agent; and the material is formed through a premixing-melt blending-in-situ grafting process. The material can be used for elevator transmission system protection components, new energy automobile components, photovoltaic support accessories and the like, is in line with the demand of strategic emerging industries, and has high industrialization feasibility.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of polymer material modification technology, specifically proposing an aging-resistant modified nylon material, its preparation method, and its application. Background Technology

[0002] Nylon, as an engineering plastic with excellent mechanical properties and good processability, has been widely used in elevator components, automotive parts, and electronic appliance housings. However, traditional nylon materials face two major problems in practical use: First, the aging protection is not comprehensive. Existing technologies mostly use a single anti-aging agent addition method, such as adding only hindered phenolic antioxidants to improve thermo-oxidative aging, or only adding benzotriazole ultraviolet absorbers to improve photo-aging resistance, resulting in a significant decrease in the protective effect of the material in complex environments. Second, the anti-aging agents have poor long-term effectiveness. Anti-aging agents are dispersed in a free state in the nylon matrix and are easily volatilized at processing temperatures of 230-260℃. They also tend to migrate to the material surface during long-term use, causing the protective performance to decline rapidly over time, making it difficult to meet the requirements of elevators, new energy vehicles, photovoltaics, and other fields for long service life.

[0003] Furthermore, to improve aging resistance, some solutions attempt to introduce nanoparticles. However, due to the high surface energy of nanoparticles and the lack of targeted modification, they tend to aggregate in the nylon matrix. This not only fails to exert a synergistic anti-aging effect but also leads to a decrease in the material's mechanical properties, requiring the addition of compatibilizers, which increases production costs and may introduce new performance shortcomings. Simultaneously, existing modification solutions are not designed to meet the specific needs of strategic emerging industries. For example, protective components for elevator transmission systems and peripheral components for new energy vehicle engines require high-temperature resistance; photovoltaic bracket accessories need long-term protection against strong outdoor ultraviolet radiation; and electronic connectors need to consider thermal cycling stability. Traditional materials cannot simultaneously meet these differentiated requirements, limiting their application in strategic emerging industries.

[0004] Further analysis reveals that the core reason for the shortcomings of traditional nylon's aging resistance lies in the free state of the anti-aging agent. On the one hand, free anti-aging agents cannot simultaneously achieve synergistic protection against thermo-oxidative and photo-aging, and the protective effect decreases by more than 50% under complex environments when added alone. On the other hand, the intermolecular forces of free anti-aging agents are weak, and they are easily volatilized at the high temperatures of 230-260℃ during nylon processing. Moreover, they migrate to the material surface during use due to the concentration gradient difference, resulting in a 50% decrease in protective efficiency after 1000 hours. This directly leads to products such as elevator transmission system protective components, new energy vehicle components, and photovoltaic brackets failing to reach their designed service life of more than 10 years.

[0005] In summary, current nylon modification technology urgently needs to overcome the fundamental bottlenecks of "incomplete aging resistance and poor long-term effectiveness," while also addressing derivative issues such as "nanoparticle aggregation and insufficient adaptability to various scenarios," in order to meet the application needs of high performance, industrialization, and multiple scenarios. Summary of the Invention

[0006] In view of this, the present invention proposes an anti-aging modified nylon material, its preparation method and application. By designing and making a self-made functionalized nanocarrier, the anti-aging agent is achieved through long-term sustained release and uniform dispersion. At the same time, the formulation and process are optimized to take into account the material's anti-aging performance, mechanical properties and application scenarios.

[0007] The technical solution of this invention is achieved as follows: This invention provides an aging-resistant modified nylon material, composed of the following components by mass percentage: 80%-98% nylon substrate, 1%-10% functionalized nanocarrier, 0.05%-0.5% auxiliary antioxidant, and 0.1%-2% grafted monomer; wherein, the functionalized nanocarrier is a composite particle of mesoporous nanospheres loaded with anti-aging agents, and is self-made through a three-step method of "mesoporous sphere preparation - surface modification - anti-aging agent loading", the anti-aging agent includes a main antioxidant and an ultraviolet absorber, which can resist both thermo-oxidative aging and photo-aging; at the same time, a method for preparing this material is provided, through a process of "premixing - melt blending - in-situ grafting" to achieve uniform composite of each component, and the application of this material in components in the strategic emerging industries.

[0008] In some embodiments, the nylon substrate is selected from PA6 or PA66, wherein the relative viscosity of PA66 is 2.4-2.8. This viscosity range can balance the melt flowability and mechanical strength of the material, avoiding part molding defects due to excessively low viscosity or processing difficulties due to excessively high viscosity.

[0009] In some embodiments, the preparation steps of the functionalized nanocarrier specifically include: First, preparation of mesoporous nanospheres: tetraethyl orthosilicate (corresponding to mesoporous silica nanospheres) or sucrose (corresponding to mesoporous carbon nanospheres) is added to an ethanol-water mixed solution, ammonia is added to adjust the pH to 9-10, the mixture is stirred at 30-60℃ for 4-8 hours, centrifuged, dried, and then calcined at 500-600℃ for 2-4 hours to obtain mesoporous nanospheres with a particle size of 30-100 nm and a pore size of 3-15 nm; Second, surface modification. Mesoporous nanospheres were added to an ethanol solution, followed by a silane coupling agent (3%-10% of the mass of the mesoporous nanospheres). The mixture was stirred at 60-90℃ for 1-4 hours, and then centrifuged and dried to obtain modified nanospheres with surface grafted amino, epoxy, or carboxyl groups. In the third step, anti-aging agent loading was performed by adding the modified nanospheres to an acetone solution, along with a main antioxidant and an ultraviolet absorber. The mixture was stirred at 50-70℃ for 3-6 hours, and the acetone was removed by vacuum distillation and dried to obtain a functionalized nanocarrier with a total anti-aging agent loading of 20%-50%.

[0010] This invention addresses fundamental technical issues through a triple design of high loading, sustained release, and preliminary compatibility of mesoporous nanospheres: 1. The structure of mesoporous nanospheres with a pore size of 5-10 nm can simultaneously load main antioxidants and ultraviolet absorbers, achieving dual protection against thermal oxidation and photoaging, breaking the limitations of traditional single protection. 2. The slow-release effect of mesoporous channels can reduce the processing volatility of anti-aging agents, prevent migration and loss during use, and extend the protective life; 3. The amino / epoxy groups grafted onto the surface by the silane coupling agent can initially improve the interfacial bonding force between the carrier and the nylon matrix, avoid the mechanical property degradation caused by nanoparticle aggregation, and lay the foundation for subsequent optimization of related issues.

[0011] In some embodiments, the mesoporous nanospheres are selected from mesoporous silica nanospheres or mesoporous carbon nanospheres, and the particle size is preferably 50-80 nm and the pore size is preferably 5-10 nm. These size parameters have been experimentally verified to ensure that the nanospheres are uniformly dispersed in the nylon matrix, avoiding agglomeration due to excessively small particle size or affecting the mechanical properties of the material due to excessively large particle size.

[0012] In some embodiments, the mass ratio of the primary antioxidant to the ultraviolet absorber in the anti-aging agent is 1:1 to 1:2. The primary antioxidant is a hindered phenolic antioxidant (such as antioxidant 1010, 1076), and the ultraviolet absorber is a benzotriazole (such as UV-327, UV-326) or a benzophenone (such as UV-531). This ratio and combination of types can synergistically exert anti-thermal and anti-photoaging effects. The 1:1 to 1:2 mass ratio can balance the protection requirements of the two types of aging and avoid performance redundancy or insufficiency caused by an excessive amount of a certain type of anti-aging agent.

[0013] In some embodiments, the primary antioxidant is preferably antioxidant 1010, and the ultraviolet absorber is preferably UV-327, with a mass ratio of 1:1.2 to 1:1.5. This specific combination and ratio can further enhance the anti-aging synergistic effect and, compared with other anti-aging agent combinations, can more effectively resist aging erosion in complex environments.

[0014] In some embodiments, the auxiliary antioxidant is selected from phosphite antioxidants, preferably antioxidant 168; the auxiliary antioxidant can form a synergistic system of "free radical capture-hydrogen peroxide decomposition" with the main antioxidant, further inhibiting the thermo-oxidative aging chain reaction and improving the long-term thermal stability of the material.

[0015] In some embodiments, the grafting monomer is selected from maleic anhydride or maleic anhydride derivatives (such as maleic anhydride-grafted polyethylene), preferably maleic anhydride, and the mass percentage is preferably 0.5%-1%. The grafting monomer can form chemical bonds on the surface of nylon molecular chains and functionalized nanocarriers through in-situ grafting reaction, thereby improving the compatibility between the two and avoiding delamination after material molding. At the same time, a reasonable amount can avoid material embrittlement due to excessive amount.

[0016] In some embodiments, the preparation method of the aging-resistant modified nylon material is as follows: First, premixing, in which nylon substrate, functionalized nanocarrier, and auxiliary antioxidant are added to a high-speed mixer and mixed for 10-20 minutes at a speed of 1500-2500 r / min and a temperature of 80-100℃ to obtain a uniform premix; Second, melt blending-in-situ grafting, in which the premix is ​​added to a twin-screw extruder, the screw speed is controlled at 180-280 r / min, the temperature of each zone of the extruder is controlled at 220-270℃, and the grafting monomer is injected into the extruder die head through a metering pump. After melt blending and in-situ grafting reaction, the material is extruded and granulated to obtain the aging-resistant modified nylon material.

[0017] In some embodiments, the application scenarios of the aging-resistant modified nylon material are to prepare protective components for elevator transmission systems (protective covers, light shields), new energy vehicle components (such as power battery shells, engine intake pipes), photovoltaic bracket accessories (such as bracket connectors, outdoor distribution box shells), or electronic and electrical connectors (such as wiring terminals, sensor shells), and to adapt to the molding requirements of different components by adjusting the injection molding temperature (230-250℃).

[0018] After solving the fundamental technical problems through functionalized nanocarriers, this invention discovered three types of derivative problems arising from the introduction of carriers, which need to be addressed synergistically through targeted derivative features: Insufficient synergy of anti-aging agents: Although the functionalized nanocarrier achieves dual anti-aging agent loading, the ratio is not optimized. Excessive amount of the main antioxidant results in insufficient protection against time aging, while excessive amount of UV absorber reduces the inhibitory effect on thermo-oxidative aging. Therefore, the mass ratio of the main antioxidant 1010 to the UV absorber UV-327 was optimized to 1:1.2-1:1.5. This ratio was verified through 20 sets of orthogonal experiments, which can avoid competitive consumption of anti-aging agents and improve synergistic efficiency by 15% compared to a 1:1 ratio. Insufficient compatibility between the carrier and nylon: Surface modification of functionalized nanocarriers can only initially improve compatibility, without forming chemical bonds, leading to easy delamination of the material and a decrease in impact strength. To address this, an in-situ grafting process using a twin-screw extruder head was employed, injecting maleic anhydride at 240-250℃ to form chemical bonds with the nylon molecular chains and the amino groups on the carrier surface. This increased interfacial bonding strength by 40% and impact strength by 30% compared to conventional blending processes. Anti-aging agent decomposition at high temperatures: Anti-aging agents on functionalized nanocarriers are easily decomposed in the high-temperature zone of extrusion, especially the auxiliary antioxidant 168, whose decomposition rate exceeds 20%. To address this, the temperature zones of the extruder were controlled separately: Zone 1 220-230℃, Zone 2 240-250℃, Zone 3 250-260℃, and the die head 240-250℃. This reduced the decomposition rate of 168 to below 5%, and improved the retention rate of thermo-oxidative aging protection by 20%.

[0019] The present invention has the following advantages over the prior art: This invention overcomes the bottlenecks of traditional nylon materials' incomplete aging protection and poor long-term effectiveness by using self-made functionalized nanocarriers. The synergistic effect of the main antioxidant and ultraviolet absorber can simultaneously resist thermal oxidative and photo-aging. The carrier's slow-release design also reduces the volatilization of anti-aging agents during processing and migration during use, significantly extending the material's protective lifespan. Simultaneously, the nanocarrier, after surface modification, can be uniformly dispersed in the nylon matrix, avoiding the mechanical property degradation caused by the agglomeration of traditional nanoparticles, and eliminating the need for additional compatibilizers, thus reducing production costs. Furthermore, through formulation and process optimization, the material can adapt to the differentiated needs of strategic emerging industries such as elevator transmission system protective components, new energy vehicles, photovoltaics, and electronics, expanding the application range of nylon materials. The overall process can be implemented using existing equipment, making it highly feasible for industrialization. It also aligns with the IPC classification requirements of strategic emerging industries, providing support for enterprises' technological layout in strategic emerging fields. Detailed Implementation

[0020] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0021] Example 1 Preparation of functionalized nanocarriers: Preparation of mesoporous silica nanospheres: 100g of tetraethyl orthosilicate was added to 500mL of ethanol-water mixture (ethanol to water volume ratio 3:1), stirred evenly, and then ammonia was added to adjust the pH to 9. The mixture was stirred at 30℃ for 8h. After the reaction was completed, the solid was centrifuged, collected and dried at 80℃, and then placed in a muffle furnace and calcined at 500℃ for 4h to obtain mesoporous silica nanospheres with a particle size of 30nm and a pore size of 3nm.

[0022] Surface modification: Weigh 50g of the above mesoporous silica nanospheres, add 300mL of ethanol, then add 3g of silane coupling agent KH-550, and stir at 60℃ for 4h; after the reaction is completed, centrifuge to separate, collect the solid and dry it to obtain modified mesoporous silica nanospheres with amino grafts on the surface.

[0023] Anti-aging agent loading: Modified mesoporous silica nanospheres were added to 300 mL of acetone, followed by 5 g of main antioxidant 1010 and 5 g of ultraviolet absorber UV-326. The mixture was stirred at 50 °C for 6 h. Then, the acetone was removed by vacuum distillation, and the solid was dried to obtain a functionalized nanocarrier with a total anti-aging agent loading of 20%.

[0024] Preparation of aging-resistant modified nylon materials: Premix: Weigh 80% PA66 (relative viscosity 2.4), 10% functionalized nanocarrier, 0.5% auxiliary antioxidant 168, and 2% maleic anhydride by mass percentage, add them to a high-speed mixer, and mix for 20 minutes at a speed of 1500 r / min and a temperature of 80℃ to obtain the premix.

[0025] Melt blending-in-situ grafting: The premixed material is added to a twin-screw extruder, the screw speed is set to 180 r / min, and the temperature of each zone of the extruder is controlled at 220-270℃; maleic anhydride is injected into the extruder head through a metering pump, and after melt blending and in-situ grafting reaction, it is extruded and granulated to obtain an aging-resistant modified nylon material.

[0026] Example 2 Preparation of functionalized nanocarriers: Preparation of mesoporous silica nanospheres: 100g of tetraethyl orthosilicate was added to 500mL of ethanol-water mixture, stirred evenly, and then ammonia was added to adjust the pH to 10. The mixture was stirred at 60℃ for 4h. After the reaction was completed, the solid was centrifuged, collected and dried at 80℃, and then placed in a muffle furnace and calcined at 600℃ for 2h to obtain mesoporous silica nanospheres with a particle size of 50nm and a pore size of 5nm.

[0027] Surface modification: Weigh 50g of the above mesoporous silica nanospheres, add 300mL of ethanol, then add 5g of silane coupling agent KH-560, and stir at 90℃ for 1h; after the reaction is completed, centrifuge to separate, collect the solid and dry it to obtain modified mesoporous silica nanospheres with surface grafted epoxy groups.

[0028] Anti-aging agent loading: Modified mesoporous silica nanospheres were added to 300 mL of acetone, followed by 8 g of main antioxidant 1010 and 10 g of ultraviolet absorber UV-327. The mixture was stirred at 70 °C for 3 h. Then, the acetone was removed by vacuum distillation, and the solid was dried to obtain a functionalized nanocarrier with a total anti-aging agent loading of 36%.

[0029] Preparation of aging-resistant modified nylon materials: Premix: Weigh 90% PA66 (relative viscosity 2.8), 7% functionalized nanocarrier, 0.2% auxiliary antioxidant 168, and 0.8% maleic anhydride by mass percentage, add them to a high-speed mixer, and mix for 15 minutes at a speed of 2200 r / min and a temperature of 90℃ to obtain the premix.

[0030] Melt blending-in-situ grafting: The premixed material is added to a twin-screw extruder, the screw speed is set to 220 r / min, and the temperature of each zone of the extruder is controlled as follows: Zone 1 230℃, Zone 2 240℃, Zone 3 250℃, and Die head 240℃. Maleic anhydride is injected into the extruder die head through a metering pump, and the grafting rate is controlled to be 1%. After melt blending and in-situ grafting reaction, the material is extruded and granulated to obtain an aging-resistant modified nylon material.

[0031] Example 3 Preparation of functionalized nanocarriers: Preparation of mesoporous carbon nanospheres: Take 100g of sucrose, add 500mL of deionized water, stir evenly, add citric acid to adjust the pH to 2, and stir at 60℃ for 4h; after the reaction is completed, centrifuge to separate, collect the solid and dry it at 120℃, and then place it in a muffle furnace at 600℃ for 2h to obtain mesoporous carbon nanospheres with a particle size of 80nm and a pore size of 10nm.

[0032] Surface modification: Weigh 50g of the above mesoporous carbon nanospheres, add 300mL of ethanol, then add 5g of silane coupling agent KH-560, and stir at 80℃ for 2h; after the reaction is completed, centrifuge to separate, collect the solid and dry it to obtain modified mesoporous carbon nanospheres with surface grafted epoxy groups.

[0033] Anti-aging agent loading: Modified mesoporous carbon nanospheres were added to 300 mL of acetone, followed by 9 g of main antioxidant 1010 and 9 g of ultraviolet absorber UV-327. The mixture was stirred at 60 °C for 4 h. Then, the acetone was removed by vacuum distillation, and the solid was dried to obtain a functionalized nanocarrier with a total anti-aging agent loading of 36%.

[0034] Preparation of aging-resistant modified nylon materials: Premix: Weigh 85% PA6, 8% functionalized nanocarrier, 0.3% auxiliary antioxidant 168, and 1.7% maleic anhydride derivative (MAH-g-PE) by mass percentage, add them to a high-speed mixer, and mix for 12 minutes at a speed of 2000 r / min and a temperature of 90℃ to obtain the premix.

[0035] Melt blending-in-situ grafting: The premixed material is added to a twin-screw extruder, the screw speed is set to 250 r / min, and the temperature of each zone of the extruder is controlled as follows: Zone 1 220℃, Zone 2 230℃, Zone 3 240℃, and Die head 230℃. Maleic anhydride derivative is injected into the extruder die head through a metering pump. After melt blending and in-situ grafting reaction, the material is extruded and granulated to obtain an aging-resistant modified nylon material.

[0036] Comparative Example 1: No carrier (only free anti-aging agent) Weigh out 80% PA66 (relative viscosity 2.4), 0.5% primary antioxidant 1010, 0.5% UV absorber UV-326, 0.5% secondary antioxidant 168, and 2% maleic anhydride by mass percentage, add them to a high-speed mixer, and mix for 20 minutes at a speed of 1500 r / min and a temperature of 80℃ to obtain a premix.

[0037] 2. Add the premixed material to a twin-screw extruder, set the screw speed to 180 r / min, and control the temperature of each zone of the extruder to 220-270℃; inject maleic anhydride into the extruder head through a metering pump, and after melt blending and in-situ grafting reaction, extrude and granulate to obtain modified nylon material.

[0038] Comparative Example 2: Unmodified nanoparticles + Free anti-aging agent Weigh out 80% PA66 (relative viscosity 2.4), 10% unmodified silica nanospheres (particle size 30nm), 0.5% primary antioxidant 1010, 0.5% UV absorber UV-326, 0.5% secondary antioxidant 168, and 2% maleic anhydride by mass percentage, add them to a high-speed mixer, and mix for 20 minutes at a speed of 1500 r / min and a temperature of 80℃ to obtain a premix.

[0039] The premixed material was added to a twin-screw extruder, the screw speed was set to 180 r / min, and the temperature of each zone of the extruder was controlled at 220-270℃. Maleic anhydride was injected into the extruder head through a metering pump. After melt blending and in-situ grafting reaction, the material was extruded and granulated to obtain the modified nylon material.

[0040] Comparative Example 3: Functionalized nanocarrier (no modification step) + free anti-aging agent Preparation of functionalized nanocarriers: Preparation of mesoporous silica nanospheres: Same as step 1.1 in Example 1.

[0041] Anti-aging agent loading: 50g of unmodified mesoporous silica nanospheres were directly added to 300mL of acetone, followed by 5g of main antioxidant 1010 and 5g of ultraviolet absorber UV-326. The mixture was stirred at 50℃ for 6h. Then, the acetone was removed by vacuum distillation, and the solid was dried to obtain the anti-aging agent loaded nanocarrier (without surface modification).

[0042] Preparation of modified nylon material: Same as step 2 in Example 1, to obtain modified nylon material.

[0043] Comparative Example 4: Functionalized nanocarrier + conventional blend (without in-situ grafting) Preparation of functionalized nanocarriers: Same as step 1 in Example 1.

[0044] Preparation of modified nylon materials: According to the formulation in step 2.1 of Example 1, maleic anhydride and other components are added together to a high-speed mixer and mixed under the same conditions to obtain a premix.

[0045] The premixed material was added to a twin-screw extruder, the screw speed was set to 180 r / min, and the temperature of each zone of the extruder was controlled at 220-270℃; direct extrusion granulation (in-situ grafting without die head) was performed to obtain modified nylon material.

[0046] Comparative Example 5: Comparative Example 2 + Additional Compatibilizer Weigh out 80% PA66 (relative viscosity 2.4), 10% unmodified silica nanospheres (particle size 30nm), 0.5% primary antioxidant 1010, 0.5% UV absorber UV-326, 0.5% secondary antioxidant 168, 2% maleic anhydride, and 3% compatibilizer POE-g-MAH by mass percentage, add them to a high-speed mixer, and mix for 20 minutes at a speed of 1500 r / min and a temperature of 80℃ to obtain a premix.

[0047] The premixed material was added to a twin-screw extruder, the screw speed was set to 180 r / min, and the temperature of each zone of the extruder was controlled at 220-270℃. Maleic anhydride was injected into the extruder head through a metering pump. After melt blending and in-situ grafting reaction, the material was extruded and granulated to obtain the modified nylon material.

[0048] Comparative Example 6: Extreme Ratio of Anti-aging Agents (1:2) Preparation of functionalized nanocarriers: Preparation of mesoporous silica nanospheres: 100g of tetraethyl orthosilicate was added to 500mL of ethanol-water mixture, stirred evenly, and then ammonia was added to adjust the pH to 10. The mixture was stirred at 60℃ for 4h. After the reaction was completed, the solid was centrifuged, collected and dried at 80℃, and then placed in a muffle furnace and calcined at 600℃ for 2h to obtain mesoporous silica nanospheres with a particle size of 50nm and a pore size of 5nm.

[0049] Surface modification: Weigh 50g of the above mesoporous silica nanospheres, add 300mL of ethanol, then add 5g of silane coupling agent KH-560, and stir at 90℃ for 1h; after the reaction is completed, centrifuge to separate, collect the solid and dry it to obtain modified mesoporous silica nanospheres with surface grafted epoxy groups.

[0050] Anti-aging agent loading: Modified mesoporous silica nanospheres were added to 300 mL of acetone, followed by 8 g of main antioxidant 1010 and 16 g of ultraviolet absorber UV-327 (mass ratio 1:2). The mixture was stirred at 70 °C for 3 h. Then, the acetone was removed by vacuum distillation, and the solid was dried to obtain a functionalized nanocarrier with a total anti-aging agent loading of 48%.

[0051] Preparation of modified nylon materials: Premix: Weigh 90% PA66 (relative viscosity 2.8), 7% functionalized nanocarrier, 0.2% auxiliary antioxidant 168, and 0.8% maleic anhydride by mass percentage, add them to a high-speed mixer, and mix for 15 minutes at a speed of 2200 r / min and a temperature of 90℃ to obtain the premix.

[0052] Melt blending-in-situ grafting: The premixed material is added to a twin-screw extruder, the screw speed is set to 220 r / min, and the temperature of each zone of the extruder is controlled as follows: Zone 1 230℃, Zone 2 240℃, Zone 3 250℃, and Die head 240℃. Maleic anhydride is injected into the extruder die head through a metering pump, and the grafting rate is controlled to be 1%. After melt blending and in-situ grafting reaction, the material is extruded and granulated to obtain modified nylon material.

[0053] Comparative Example 7: PA6 + Unmodified Mesoporous Carbon Support Preparation of functionalized nanocarriers: Preparation of mesoporous carbon nanospheres: Take 100g of sucrose, add 500mL of deionized water, stir evenly, add citric acid to adjust the pH to 2, and stir at 60℃ for 4h; after the reaction is completed, centrifuge to separate, collect the solid and dry it at 120℃, and then place it in a muffle furnace at 600℃ for 2h to obtain mesoporous carbon nanospheres with a particle size of 80nm and a pore size of 10nm.

[0054] Anti-aging agent loading: Take 50g of the above unmodified mesoporous carbon nanospheres and add them to 300mL of acetone, then add 9g of the main antioxidant 1010 and 9g of the ultraviolet absorber UV-327, and stir at 60℃ for 4h; then remove the acetone by vacuum distillation, dry the solid, and obtain an unmodified mesoporous carbon support with a total anti-aging agent loading of 36%.

[0055] Preparation of modified nylon materials: Premix: Weigh 85% PA6, 8% unmodified mesoporous carbon support, 0.3% auxiliary antioxidant 168, and 1.7% maleic anhydride derivative (MAH-g-PE) by mass percentage, add them to a high-speed mixer, and mix for 12 minutes at a speed of 2000 r / min and a temperature of 90℃ to obtain the premix.

[0056] Melt blending-in-situ grafting: The premixed material is added to a twin-screw extruder, the screw speed is set to 250 r / min, and the temperature of each zone of the extruder is controlled as follows: Zone 1 220℃, Zone 2 230℃, Zone 3 240℃, and Die head 230℃. Maleic anhydride derivative is injected into the extruder die head through a metering pump. After melt blending and in-situ grafting reaction, the material is extruded and granulated to obtain modified nylon material.

[0057] Performance verification 1. Anti-aging agent retention rate test: Take the materials before and after extrusion granulation in Examples 1-3 and Comparative Examples 1-5 respectively, and determine the content of anti-aging agents (1010, UV-326 / UV-327) by high performance liquid chromatography, and calculate the retention rate (anti-aging agent content after granulation / anti-aging agent content before granulation × 100%).

[0058] 2. Xenon Lamp Aging Performance Test: The materials prepared in each example were injection molded into standard tensile specimens and subjected to a 5000-hour aging test in a xenon lamp aging test chamber (irradiance 0.71 W / m²) according to GB / T16422.2-2014. 2 (@340nm, black standard temperature 63℃, relative humidity 50%), tensile strength was tested before and after aging according to GB / T1040.2-2006, and the tensile strength retention rate was calculated as (tensile strength after aging / tensile strength before aging × 100%).

[0059] 3. Impact strength test: The materials prepared in each example were injection molded into standard impact specimens, and the notched impact strength was tested using a simply supported beam impact testing machine in accordance with GB / T1043.1-2008.

[0060] 4. Observation of dispersion uniformity and stratification: The materials prepared in each case were sliced ​​and the dispersion of nanoparticles was observed using a scanning electron microscope; at the same time, the materials were injection molded into 100mm×100mm×2mm samples and placed at room temperature for 30 days to observe whether stratification occurred.

[0061] Performance results:

[0062] Based on performance verification data and the differences in technical solutions among the examples, it can be seen that Example 1, which uses a "basic mesoporous silica nanocarrier (particle size 30nm, pore size 3nm) + standard mixing-extrusion process," achieves anti-aging agent loading and sustained release through the mesoporous carrier. The anti-aging agent retention rate reaches 95%, and the tensile strength retention rate is 80% after 5000 hours of xenon lamp aging, with an impact strength of 8.0 kJ / m. 2The nanoparticles are uniformly dispersed, which solves the core problems of incomplete aging resistance and poor long-term effectiveness of traditional nylon. Example 2, based on Example 1, optimizes the mesoporous carrier size (particle size 50nm, pore size 5nm), the anti-aging agent ratio (1010 to UV-327 mass ratio 1:1.25), and the extrusion zone temperature control process (zone 1 230℃, zone 2 240℃, zone 3 250℃, die head 240℃), and controls the maleic anhydride grafting rate to 1%. Compared to Example 1, the performance is further improved, with the anti-aging agent retention rate increasing to 97%, the tensile strength retention rate after aging reaching 85%, and the impact strength reaching 8.5kJ / m². 2 Furthermore, the material showed no yellowing or delamination, demonstrating the synergistic effect of carrier size optimization, anti-aging agent ratio adjustment, and zoned temperature control process. This can further optimize aging resistance and mechanical properties while addressing the core issues. Example 3 used mesoporous carbon nanospheres (80nm particle size, 10nm pore size) as a carrier, combined with maleic anhydride derivative (MAH-g-PE), and employed extrusion temperatures adapted to PA6 substrate (zone 1 220℃, zone 2 230℃, zone 3 240℃, die head 230℃). The anti-aging agent retention rate was 96%, the tensile strength retention rate after aging was 82%, and the impact strength was 8.3kJ / m. 2 This verified the compatibility of different mesoporous carrier materials with substrates and expanded the application scope of the solution.

[0063] In contrast, Comparative Example 1 did not use a mesoporous carrier; only free anti-aging agents were added directly. The retention rate of the processed anti-aging agent was only 68%, and the tensile strength retention rate after aging was only 52%, highlighting the crucial role of the mesoporous carrier in improving the long-term effectiveness of anti-aging. Comparative Example 2 used unmodified silica nanospheres combined with free anti-aging agents; the nanoparticles showed severe aggregation, and the impact strength was only 5.8 kJ / m². 2 This demonstrates the necessity of carrier surface modification; Comparative Example 3, omitting the mesoporous carrier surface modification step, still exhibits partial agglomeration despite being loaded with an anti-aging agent, resulting in an impact strength of 6.2 kJ / m. 2 The tensile strength retention rate after aging was 55%, further confirming the influence of surface modification on carrier dispersibility and anti-aging effect; Comparative Example 4 did not use the in-situ grafting process at the die head, and maleic anhydride was mixed and extruded with other components. The material showed slight delamination, and the impact strength was 6.5 kJ / m. 2 This demonstrates the importance of in-situ grafting in improving the compatibility between the carrier and the nylon matrix; Comparative Example 5, with the addition of compatibilizer POE-g-MAH to Comparative Example 2, still exhibits a small amount of agglomeration, and its impact strength is 6.0 kJ / m. 2 The tensile strength retention rate after aging was 53%, proving that even the addition of compatibilizers cannot replace the synergistic effect of "mesoporous carrier modification + in-situ grafting" in this solution.

[0064] In summary, this invention effectively addresses the performance shortcomings of traditional modified nylon through the synergistic combination of mesoporous carrier design, anti-aging agent loading and ratio optimization, in-situ grafting, and zoned temperature control processes. Furthermore, the technical adjustments and performance improvements in each embodiment form a clear correspondence, and the technical effects are significantly better than those of comparative examples lacking core technical means or using traditional solutions. The innovation and practicality of the solution are evident.

[0065] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A method for preparing an aging-resistant modified nylon material, characterized in that, The aging-resistant nylon modified material is composed of the following raw materials in the following mass percentages: PA66 80%-98%, functionalized nanocarrier 1%-10%, antioxidant 168 0.05%-0.5%, and maleic anhydride 0.5%-1%; the relative viscosity of PA66 is 2.4-2.8; the functionalized nanocarrier is a composite particle of mesoporous silica nanospheres loaded with anti-aging agents, the mesoporous silica nanospheres have a particle size of 50-80 nm and a pore size of 5-10 nm, the total loading of anti-aging agents is 20%-50% of the mass of the mesoporous silica nanospheres, and the anti-aging agents are composed of antioxidant 1010 and ultraviolet absorber UV-327, with a mass ratio of 1:(1.2-1.5); the preparation method includes the following steps: (1) Preparation of mesoporous silica nanospheres: Tetraethyl orthosilicate was added to an ethanol-water mixture, ammonia was added to adjust the pH to 9-10, the mixture was stirred at 30-60℃ for 4-8h, centrifuged and dried, and then calcined at 500-600℃ for 2-4h to obtain the mesoporous silica nanospheres. (2) Surface modification: The mesoporous silica nanospheres are added to an ethanol solution, and a silane coupling agent is added. The amount of the silane coupling agent is 3%-10% of the mass of the mesoporous silica nanospheres. The reaction is carried out at 60-90℃ for 1-4 hours, and then centrifuged and dried to obtain modified mesoporous silica nanospheres. (3) Anti-aging agent loading: The modified mesoporous silica nanospheres were added to an acetone solution, antioxidant 1010 and ultraviolet absorber UV-327 were added, and the reaction was carried out at 50-70℃ for 3-6 hours. The acetone was removed and the mixture was dried to obtain the functionalized nanocarrier. (4) Premixing: Add PA66, functionalized nanocarrier and antioxidant 168 to a high-speed mixer and mix for 12-15 min at a speed of 1800-2200 r / min and a temperature of 80-100℃ to obtain a premix; (5) Melt blending-in-situ grafting: The premixed material is added to a twin-screw extruder with a screw speed of 180-280 r / min, a zone 1 temperature of 220-230℃, a zone 2 temperature of 240-250℃, a zone 3 temperature of 250-260℃, and a die head temperature of 240-250℃; maleic anhydride is injected into the die head of the extruder through a metering pump, the injection rate of maleic anhydride is matched with the extrusion rate, and the grafting rate is controlled to be 0.5%-1.5%. After melt blending and in-situ grafting, the material is extruded and granulated to obtain an aging-resistant modified nylon material.

2. The preparation method according to claim 1, characterized in that, The mesoporous silica nanospheres have a particle size of 50 nm and a pore size of 5 nm. The total loading of the anti-aging agent is 36%, and the mass ratio of antioxidant 1010 to ultraviolet absorber UV-327 is 1:1.

25.

3. The preparation method according to claim 2, characterized in that, In step (2), 50g of mesoporous silica nanospheres were added to 300mL of ethanol and 5g of silane coupling agent KH-560, and reacted at 90℃ for 1h. In step (3), the modified mesoporous silica nanospheres were added to 300mL of acetone, and 8g of antioxidant 1010 and 10g of ultraviolet absorber UV-327 were added, and reacted at 70℃ for 3h.

4. The preparation method according to any one of claims 1-3, characterized in that, In step (4), the high-speed mixer has a rotation speed of 2200 r / min, a temperature of 90℃, and a mixing time of 15 min; in step (5), the twin-screw extruder has a screw speed of 220 r / min, a zone 1 temperature of 230℃, a zone 2 temperature of 240℃, a zone 3 temperature of 250℃, a die head temperature of 240℃, and a grafting rate of 1%.

Citation Information

Patent Citations

  • Nylon 66 compound capable of use for weaving glass-fiber-free shuttle

    CN101760021A

  • Halloysite nano-tubes grafted and loaded with anti-aging agent, preparation method and applications thereof

    CN110734581A

  • High-temperature nylon and preparation method thereof

    CN114031938A